2020
DOI: 10.1136/bmjoq-2018-000572
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal lesions found incidentally: how to improve clinical and cost-effectiveness

Abstract: IntroductionAdrenal incidentalomas are lesions that are incidentally identified while scanning for other conditions. While most are benign and hormonally non-functional, around 20% are malignant and/or hormonally active, requiring prompt intervention. Malignant lesions can be aggressive and life-threatening, while hormonally active tumours cause various endocrine disorders, with significant morbidity and mortality. Despite this, management of patients with adrenal incidentalomas is variable, with no robust evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…Its prevalence diff ers in distinct risk populations and generally varies between 0.4-10%. [1][2][3] Th e tumors are located bilaterally in 10-15% of cases with adrenal incidentaloma. [4][5] Most of the cases are benign and only 0.7-5% are malignant.…”
Section: Introductionmentioning
confidence: 99%
“…Its prevalence diff ers in distinct risk populations and generally varies between 0.4-10%. [1][2][3] Th e tumors are located bilaterally in 10-15% of cases with adrenal incidentaloma. [4][5] Most of the cases are benign and only 0.7-5% are malignant.…”
Section: Introductionmentioning
confidence: 99%
“…To address this gap, we have recently developed a cost-effectiveness tool for adrenal incidentaloma management. 8 We have initiated discussions with the lung cancer screening programme to support their efforts in establishing a clinicallyand cost-effective strategy to address adrenal incidentalomas. Such initiatives are essential if the NHS is to address this potential clinical risk.…”
Section: E203mentioning
confidence: 99%
“…Adrenal incidentaloma (AI) is a common endocrine condition, and it is defined as an adrenal mass of greater than 1 cm in diameter detected incidentally when performing radiological studies to evaluate a non-adrenal condition or disease. A multidisciplinary workup with a careful laboratory and radiological analysis is required to make a correct diagnosis of the condition and ensure its effective management [ 1 , 2 ]. While AIs are non-functional and benign in most cases, they can be malignant or secreting in approximately 20% of cases [ 1 - 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown an increase in the prevalence of AIs with advancing age, with peak incidences occurring between the fifth and seventh decades of life [ 1 ]. They are rarely found in patients younger than 30 years of age, and hence such cases, if encountered, should be investigated promptly due to the potential risk of ACC or functional lesions [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation